First Total Synthesis of (–)-Auranomide C and Its Derivatives - Sorra, Kumaraswamy; Mukkanti, K.; Pusuluri, Srinivas (Synthesis, 2014)
The first total synthesis of (–)-auranomide C has been achieved. The short synthetic strategy involves a reductive dehydrocyclization and the nucleophilic ring opening of a fused γ-lactam. The route allows for ease in synthesizing diverse derivatives in the side chain of the natural product.
Keywords: auranomide; quinazolinobenzodiazepine; intramolecular cyclization; reductive dehydrocyclization; nucleophilic ring opening